Political Dynamic of The Era Pre-Prophetic 570-610 AD: (Contribution of The Political System in Islamic Civilization) - Ferdiansyah, Novan; Mubaraq, Zulfi; Kholid, Nur; Maimun; Kurnia, Fini Adila (Islah: Journal of Islamic Literature and History, 2024)
The Study of Islamic Civilization Pre-prophethic are very important to study in more depth. This is because these studies never stop being debated. The aim of this article is to understand 3 things: First, the political paradigm of the Pre-Prophetic Period. Second, internal and external factors that influenced the politics of the Pre-Prophetic Period. Third, the positive and negative implications of the politics of the Pre-Prophetic Period on Muslims. The method used is qualitative research with a literature review approach based on Mustika Zed theory. The data was collected using library research techniques and analyzed using collection, reduction, display and conclusion drawing techniques. The results found were 3 things: First, the political paradigm of the pre-prophetic period (570-610 AD) had 3 forms: (1) Absolute Monarchy (2) Oligarchy of Power (3) Tribal Confederation. Second, internally, there were 3 factors that influenced the politics of the pre-prophetic period: (1) Nepotism of the rulers (2) Patriarchy and social caste (3) conflict of interests of the rulers. Externally, there were 3 factors that influenced the politics of the pre-prophetic period: (1) Geographical location and economic system (2) limited natural resources (3) Arab war traditions. Third, there are 3 positive implications of pre-prophetic politics for Muslims: (1) Social cohesion within tribes (2) maintenance of local culture and traditions (3) Diversity of political systems. Meanwhile, there are 3 negative implications of pre-prophetic politics on Muslims: (1) conflict and war between tribes (2) discrimination and social inequality (3) lagging behind in economic development. The conclusion that this article shows is that it provides new views and insights into politics in the pre-prophetic period (570-610 AD).